Glymphatic dysfunction is related to motor disability fully mediated by gray matter degeneration in early-stage Parkinson's disease - Zihao Zhu; Xiaojie Duanmu; Cheng Zhou; Jiaqi Wen; Jianmei Qin; Qianshi Zheng; Weijin Yuan; Tao Guo; Haoting Wu; Chenqing Wu; Jingwen Chen; Jingjing Wu; et al. (Neurobiology of Disease, 2025)
Background: Glymphatic dysfunction plays a critical role in Parkinson's disease (PD), but its impact on neurodegeneration and clinical symptoms in the early-stage remains unclear. This study investigates the relationship between glymphatic dysfunction, gray matter (GM) degeneration, and clinical deterioration in early-stage PD. Methods: A total of 249 early-stage PD patients and 114 healthy controls (HC) underwent T1-weighted and DTI scans, along with clinical assessments. Among them, 83 patients and 32 HC were longitudinally re-visited. The diffusion tensor imaging along the perivascular space (DTI-ALPS) index was used to estimate glymphatic function. Linear mixed model was performed to identify longitudinal GM degeneration and clinical deterioration; partial correlation analysis was applied to explore GM degeneration associated with glymphatic dysfunction; while mediation analysis was conducted to investigate the mediation role of GM degeneration in the relationship between glymphatic dysfunction and clinical deterioration. Results: Significantly lower DTI-ALPS index was observed in PD patients, which correlated with reduced cortical thickness in the bilateral posterior cingulate and left lingual gyrus at baseline, and faster atrophy in the left rostral anterior cingulate during follow-up. The relationship between DTI-ALPS index and baseline motor disability was fully mediated by the degeneration of the left posterior cingulate. Conclusion: Glymphatic dysfunction in early-stage PD correlates with GM degeneration and motor decline. Left posterior cingulate degeneration fully mediates the impact of glymphatic dysfunction on motor disability. These findings deepen the understanding of the clinical relevance of glymphatic dysfunction and provide further insights into the regulatory mechanisms underlying PD-related neurodegenerative circuits.